COOPERATION OF UZBEKISTAN WITH FOREIGN COUNTRIES IN THE FIELD OF AGRICULTURE - Ibragimov Muzaffar (Western European Studies, 2025)
This article analyzes the cooperation of the Republic of Uzbekistan with foreign countries in the agricultural sector. In particular, it covers the international exchange of experience in the modernization of agriculture, the introduction of innovative technologies, the development of water-saving systems and advanced seed production methods. The article analyzes the economic, environmental and social effectiveness of this cooperation, as well as its role in improving the well-being of the rural population
Keywords: Uzbekistan; agriculture; international cooperation